Pemberdayaan Umkm Dan Penguatan Kohesi Sosial Melalui Program Kkn Tematik Di Kelurahan Samangraya, Kota Cilegon: Pengabdian - Dewi Agustina Solihin; Putri Ayu Permata Devi; Roihan Aldi Pratama (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Community service is one of the pillars of the Tri Dharma of Higher Education, aimed at applying knowledge to provide solutions to societal problems. This service research was carried out in Samangraya Village, Citangkil District, Cilegon City, which has the potential for Micro, Small, and Medium Enterprises (MSMEs), but faces challenges in business organization, promotion, and branding. Additionally, social challenges, such as low youth participation, are also a concern. The method used in this program is Participatory Action Research (PAR), where students collaborate actively with the community to identify problems, design, and implement programs. This activity took place from July 21 to August 25, 2025, and included several main programs: shop layout redesign, promotional media design (banners), product logo creation, MSME seminars, and participation in social activities such as the commemoration of Indonesia’s 80th Independence Day. he results of this activity showed significant positive impacts, including an increase in visual appeal and store comfort, the creation of a product’s visual identity through logos and banners, expanded marketing knowledge for MSME actors, and strengthened community solidarity. This program proves that thematic Community Service (KKN) with a participatory approach is effective in empowering the local economy while also strengthening social cohesion within the community.